Stride toward freedom : the Montgomery story - King, Martin Luther, Jr (Ballantine books ;, 1958)
Chronicles the Montgomery, Alabama bus boycott sparked by Mrs. Rosa Park's refusal to give up her seat to a white male, describing the plans and problems of a nonviolent campaign, reprisals by the white community, and the eventual attainment of desegrated city bus service.